2024
DOI: 10.2463/mrms.mp.2022-0112
|View full text |Cite
|
Sign up to set email alerts
|

Thin-slice Two-dimensional T2-weighted Imaging with Deep Learning-based Reconstruction: Improved Lesion Detection in the Brain of Patients with Multiple Sclerosis

Abstract: Purpose: Brain MRI with high spatial resolution allows for a more detailed delineation of multiple sclerosis (MS) lesions. The recently developed deep learning-based reconstruction (DLR) technique enables image denoising with sharp edges and reduced artifacts, which improves the image quality of thin-slice 2D MRI. We, therefore, assessed the diagnostic value of 1 mm-slice-thickness 2D T2-weighted imaging (T2WI) with DLR (1 mm T2WI with DLR) compared with conventional MRI for identifying MS lesions.Methods: Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Similarly, Iwamura et al 32 have investigated a similar hypothesis for thin-slice brain imaging in 42 patients with multiple sclerosis (MS). In their study, the authors compared conventional 5 mm 2D T2WI with 1 mm 2D T2WI and applied a DL-based reconstruction software (AIR Recon DL) to the latter.…”
Section: Applications In Brain Imagingmentioning
confidence: 99%
“…Similarly, Iwamura et al 32 have investigated a similar hypothesis for thin-slice brain imaging in 42 patients with multiple sclerosis (MS). In their study, the authors compared conventional 5 mm 2D T2WI with 1 mm 2D T2WI and applied a DL-based reconstruction software (AIR Recon DL) to the latter.…”
Section: Applications In Brain Imagingmentioning
confidence: 99%
“…DLR learns to reconstruct images by recognizing patterns of low resolution and noise through training on previous data, thereby reconstructing only the ideal image [ 15 ]. Although previous studies have shown improved SNR and contrast-to-noise ratio (CNR) using DLR techniques [ 16 17 18 19 20 21 ], the utility of DLR for detecting abnormalities in the diagnosis of TLE has not been evaluated. We hypothesized that 1.5-mm slice-thickness oblique coronal 2D turbo spin echo T2-weighted imaging reconstructed with DLR (1.5-mm MRI + DLR) would be superior to routine 3-mm slice-thickness oblique coronal 2D turbo spin echo T2-weighted imaging (routine MRI) and 1.5-mm slice thickness MRI without DLR (1.5-mm MRI without DLR) in detecting focal lesions in patients with TLE.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, significant advancements in machine learning have gained great attention in the field of medical imaging [15]. Applied to image reconstruction, these deep learning (DL) techniques provide an improved trade-off between speed, resolution and signal-to-noise ratio (SNR), and often enable significant reductions in scan times when combined with (highly) accelerated conventional techniques such as parallel imaging (PI) [16][17][18][19]. Alternative methods include compressed sensing (CS) [20][21][22][23], simultaneous multislice (SMS) imaging (also known as multiband imaging) [24][25][26][27][28], iterative denoising (ID) [29,30] and synthetic MRI [31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%